Ultra-Rapid Drug Susceptibility Testing for Klebsiella pneumoniae Clinical Isolates in 60 Min by SYBR Green I/Propidium Iodide Viability Assay - Chen, Jiazhen; Wang, Xuyang; Wang, Shiyong; Chen, Chen; Zhang, Wenhong; Zhang, Ying (Frontiers in Microbiology, 2021)
Background: We aimed to optimize and validate the drug susceptible test (DST) assay by SYBR Green I/PI (SG-PI) method using a panel of 89 Klebsiella pneumoniae clinical isolates in comparison with the conventional DST method to three most important antibiotics used for treatment of this bacterial infection, including imipenem, cefmetazole and gentamicin. Methods: By staining with SYBR Green I and PI dyes, green fluorescence and red fluorescence, which linearly correlated with the percentages of live and dead or membrane damaged cells, respectively, were used to produce two standard curves to calculate the relative cell membrane impermeable rates for each log and stationary phase cultures. Stationary phase K. pneumoniae cells were used in imipenem and cefmetazole SG-PI DST assay whereas log phase cells were used in the gentamicin assay. The conventional broth microdilution method was used as a gold standard for DST for comparison. Results: Data showed that after antibiotic treatment for 30 to 60 minutes, the antibiotic-resistant K. pneumoniae strains had significantly higher numbers of surviving cells than the susceptible strains at different concentrations of imipenem, cefmetazole and gentamicin, where the average relative membrane impermeable rates were 88.5%, 92.5% and 103.8% for resistant clinical strains, respectively, and 9.1%, 49.3% and 71.5% for susceptible strains, respectively. Overall, the total concordances between the ultra-rapid SG-PI method and conventional minimal inhibitory concentration assay in diagnosing imipenem, cefmetazole and gentamicin resistance were high and were 96.6% (86/89), 95.4% (83/87) and 95.5% (85/89), respectively. Conclusions: We demonstrate that our novel SG-PI assay can accurately and stably detect resistance to different antibiotics in clinical isolates of K. pneumonia in an ultra-fast manner in 60 to 90 minutes.